A Mixture of Phenolic Metabolites of Quercetin Can Decrease Elevated Blood Pressure of Spontaneously Hypertensive Rats Even in Low Doses - Najmanová, Iveta; Pourová, Jana; Mladěnka, Přemysl (Nutrients, 2020)
Quercetin is proven to decrease arterial blood pressure when given orally. Its bioavailability is, however, low and, therefore, its metabolites could rather be responsible for this effect. In particular, the colonic metabolites of quercetin, 3,4-dihydroxyphenylacetic acid (DHPA), 4-methylcatechol (4MC), and 3-(3-hydroxyphenyl)propionic acid (3HPPA), have been previously shown to decrease the blood pressure in spontaneously hypertensive rats (SHR). Interestingly, the mechanisms of action of these three metabolites are different. The aim of this study is hence to investigate if these metabolites can potentiate each other and thus decrease blood pressure in reduced doses. Three double-combinations of previously mentioned metabolites were administered to SHR as infusions to mimic a real biological situation. All combinations significantly decreased the blood pressure in SHR but there were important differences. The effect of DHPA and 4MC was mild and very short. A combination of DHPA with 3HPPA caused more pronounced effects, which were also rather short-lived. The last combination of 3HPPA and 4MC caused a long-lasting effect. In conclusion, certain combinations of quercetin metabolites have a more pronounced antihypertensive effect than single metabolites.
Keywords: katecholy; modely nemocí na zvířatech; Quercetin; Male; antihypertenziva; hypertenze; Coumaric Acids; in vivo; potkani inbrední SHR; vztah mezi dávkou a účinkem léčiva; 3,4-Dihydroxyphenylacetic Acid; mužské pohlaví; infusion; rat; fenoly; Hypertension; blood pressure; krysa rodu Rattus; biologická dostupnost; Animals; krevní tlak; phenolic; kyselina 3,4-dihydroxyfenyloctová; zvířata; Catechols; Rats; Antihypertensive Agents; Blood Pressure; kyseliny kumarové; Disease Models, Animal; Rats, Inbred SHR; Biological Availability; Phenols; Dose-Response Relationship, Drug; quercetin